Contrast in atomically resolved EF-SCEM imaging - Wang, P; D'Alfonso, A; Hashimoto, A; Morgan, A; Takeguchi, M; Mitsuishi, K; Shimojo, M; Kirkland, A; Allen, L; Nellist, P (2013)
Energy-filtered scanning confocal electron microscopy (EF-SCEM) is a technique that uses the reduced depth of field of an aberration-corrected transmission electron microscope to provide three-dimensional (3D) compositional information. Using a silicon sample in the <110> orientation, we show that EF-SCEM image data can be recorded that shows lattice resolution in the plane perpendicular to the incident beam direction. The confocal effect is demonstrated through the reduction of the mean intensity as the confocal plane is displaced from the sample mid-plane, unlike optical sectioning in high-angle annular dark-field scanning transmission electron microscopy (STEM). Simulations of the EF-SCEM data show agreement with the experimental data, and allow the interpretability of the data to be explored. The effects of channelling, absorption and delocalisation complicate the quantitative and qualitative interpretation of the data, highlighting the need for matching to simulations. Finally the effects of the finite detector pin-hole aperture size are explored, and we show that the EF-SCEM contrast in the plane perpendicular to the beam direction starts to resemble that of a STEM spectrum imaging experiment as the aperture size increases. © 2013 Elsevier B.V.